2018
DOI: 10.1097/tp.0000000000002283
|View full text |Cite
|
Sign up to set email alerts
|

Local Injections of Tacrolimus-loaded Hydrogel Reduce Systemic Immunosuppression-related Toxicity in Vascularized Composite Allotransplantation

Abstract: Our findings demonstrate that localized immunosuppression with TAC hydrogel is a long-term safe and reliable treatment. It may reduce the burden of systemic immunosuppression in vascularized composite allotransplantation, potentially boosting the clinical application of this surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…When used in a VCA model, the ipsilateral injection of Rapa-ISFI promoted graft survival for >100 days. This consistent with the results achieved by other drug delivery systems such as FK506-loaded hydrogels 6,7 or biodegradable disks containing FK506-loaded double-walled microspheres 9 , confirming that in situ delivery of immunosuppressive drugs is a feasible and promising approach in VCA. However, in contrast to FK506 hydrogels, ISFI presented a limited burst release that remained in the clinically relevant range.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When used in a VCA model, the ipsilateral injection of Rapa-ISFI promoted graft survival for >100 days. This consistent with the results achieved by other drug delivery systems such as FK506-loaded hydrogels 6,7 or biodegradable disks containing FK506-loaded double-walled microspheres 9 , confirming that in situ delivery of immunosuppressive drugs is a feasible and promising approach in VCA. However, in contrast to FK506 hydrogels, ISFI presented a limited burst release that remained in the clinically relevant range.…”
Section: Discussionsupporting
confidence: 88%
“…Unlike solid organ transplantation, VCA offers unique opportunities for local delivery of immunosuppressive agents directly to the graft 3 . We and other groups have shown that site-specific immunosuppression can be successfully used in VCA employing topical FK506 4,5 and clobetasol 5 , hydrogel-based drug delivery systems laden with FK506 6,7 , intra-graft injections of FK506 8 , and biodegradable disks containing FK506-loaded microspheres 9 . All these approaches aim to reduce systemic exposure and global collateral or end-organ adverse effects while maintaining therapeutic levels in the different tissues of the grafts, especially skin.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed TGMS-TAC, a hydrogel for localized immunosuppressive drug delivery directly into a transplant graft. Our findings in a rat VCA model suggest that TGMS-TAC is an efficient and safe alternative to systemic immunosuppression [ 8 ] Here we aimed at expanding our understanding and the clinical translatability of this therapeutic modality. Previously, we have shown in vitro , that TGMS-TAC acts in an on-demand manner, by releasing TAC in response to enzymes typically elevated during rejection-induced inflammation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the dependency of TAC release on an inflammatory reaction has not yet been demonstrated in vivo . Moreover, we reported that repeated intra-graft TGMS-TAC injections in a Brown Norway-to-Lewis rat hind-limb transplantation model prolonged graft survival for >280 days, with sub-therapeutic drug levels in blood for extended periods of time [ 8 ], making this approach a promising alternative to systemic immunosuppression in VCA patients. Although targeted immunosuppression has the potential to increase therapeutic index, currently only the topical application of TAC is used in the clinic to treat rejection in VCA patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers are widely used as sustainable drug delivery vehicles due to their advantages such as easily fabricated, encapsulation of a variety of drugs, and predictable biodegradability . Moreover, many studies have confirmed that biodegradable polymer‐encapsulated immunosuppressants prolong the survival of allograft without significant adverse effects , indicating that biodegradable microspheres could be a novel drug delivery system for VCA site‐specific immunosuppression. Poly lactic‐co‐glycolic acid (PLGA) is widely used as a biodegradable material for fabrication of polymeric nanoparticles .…”
Section: Introductionmentioning
confidence: 99%